Technical Note: Validation and implementation of a wireless transponder tracking system for gated stereotactic ablative radiotherapy of the liver. Issue 6 (11th May 2016) - James, Joshua; Cetnar, Ashley; Dunlap, Neal E.; Huffaker, Corinna; Nguyen, Vi Nhan; Potts, Melissa; Wang, Brian
Abstract : Purpose: Tracking soft‐tissue targets has recently been cleared as a new application of Calypso, an electromagnetic wireless transponder tracking system, allowing for gated treatment of the liver based on the motion of the target volume itself. The purpose of this study is to describe the details of validating the Calypso system for wireless transponder tracking of the liver and to present the clinical workflow for using it to deliver gated stereotactic ablative radiotherapy (SABR). Methods: A commercial 3D diode array motion system was used to evaluate the dynamic tracking accuracy of Calypso when tracking continuous large amplitude motion. It was then used to perform end‐to‐end tests to evaluate the dosimetric accuracy of gated beam delivery for liver SABR. In addition, gating limits were investigated to determine how large the gating window can be while still maintaining dosimetric accuracy. The gating latency of the Calypso system was also measured using a customized motion phantom. Results: The average absolute difference between the measured and expected positional offset was 0.3 mm. The 2%/2 mm gamma pass rates for the gated treatment delivery were greater than 97%. When increasing the gating limits beyond the known extent of planned motion, the gamma pass rates decreased as expected. The 2%/2 mm gamma pass rate for a 1, 2, and 3 mm increase in gating limits was measured to be 97.8%, 82.9%, and 61.4%, respectively. The average gating latency was measured to be 63.8 ms for beam‐hold and 195.8 ms for beam‐on. Four liver patients with 17 total fractions have been successfully treated at our institution. Conclusions: Wireless transponder tracking was validated as a dosimetrically accurate way to provide gated SABR of the liver. The dynamic tracking accuracy of the Calypso system met manufacturer's specification, even for continuous large amplitude motion that can be encountered when tracking liver tumors close to the diaphragm. The measured beam‐hold gating latency was appropriate for targets that will traverse the gating limit each respiratory cycle causing the beam to be interrupted constantly throughout treatment delivery.